2005
DOI: 10.1103/physrevb.71.134401
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic ground state ofCeNi1xCux: A calorimetric investigation

Abstract: CeNi 1−x Cu x is a substitutional magnetic system where the interplay of the different magnetic interactions leads to the disappearance of the long-range magnetic order on the CeNi side. The existence of inhomogeneities ͑spin clusters or phase coexistence͒ has been previously detected by magnetization and muon spin relaxation ͑SR͒ spectroscopy measurements. These inhomogeneities are always observed regardless of the different preparation methods and must, then, be considered as intrinsic. We present a detailed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
47
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 52 publications
7
47
0
Order By: Relevance
“…Thus, a SG-Kondo transition has been observed experimentally with increasing concentration in disordered alloys around the QCP. Recent experiments performed in CeNi 1 À x Cu x alloys have shown that the phase diagram of these alloys is more complicated [51,52]. In fact, when temperature decreases, for alloys with 0.7 > x > 0.1, there appears a ''cluster spin glass'' phase presenting magnetic inhomogeneities, rather than a classical SG phase.…”
Section: The Kondo Lattice-spin Glass Competitionmentioning
confidence: 99%
“…Thus, a SG-Kondo transition has been observed experimentally with increasing concentration in disordered alloys around the QCP. Recent experiments performed in CeNi 1 À x Cu x alloys have shown that the phase diagram of these alloys is more complicated [51,52]. In fact, when temperature decreases, for alloys with 0.7 > x > 0.1, there appears a ''cluster spin glass'' phase presenting magnetic inhomogeneities, rather than a classical SG phase.…”
Section: The Kondo Lattice-spin Glass Competitionmentioning
confidence: 99%
“…(6) seems to be more adequate here than the "average" description used for example in the Sherrington-Kirkpatrick approach [45,47]. However, a real improvement will be provided by trying to describe better the clusters which are yielding the CG state with ferromagnetic correlations and the IFM state and then the observed percolative CG-IFM transition observed with decreasing temperature [37,38]. A first approach had been proposed to obtain clusters with intrasite Kondo interactions and both intra-and inter-cluster magnetic interactions within the Sherrington-Kirkpatrick approach [53].…”
Section: The Spin Glass-kondo-magnetic Order Competitionmentioning
confidence: 99%
“…The first studied case is the CeNi x Cu 1−x alloys [35][36][37][38][39], but recently the CeRh x Pd 1−x alloys [40,41] have been also studied and a new cluster glass state has been identified recently in these two cases. In fact, a careful experimental study of CeRh x Pd 1−x alloys shows the presence of the Kondo clusters near x = 0.8 when the ferromagnetic phase is very close to disappear [40].…”
Section: The Spin Glass-kondo-magnetic Order Competitionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a real improvement will be provided by trying to describe better the clusters which are yielding the cluster-glass state (CG) with ferromagnetic correlations and the IFM state and also the observed percolative CGIFM transition observed with decreasing temperature [46,47]. A rst approach had been proposed to obtain clusters with intrasite Kondo interactions and both intra-and inter-cluster magnetic interactions within the SherringtonKirkpatrick approach [58].…”
Section: (1005)mentioning
confidence: 99%